2018
DOI: 10.1002/jsfa.9354
|View full text |Cite
|
Sign up to set email alerts
|

Alternative food matrices for snack formulations in terms of acrylamide formation and mitigation

Abstract: These new vegetable snacks could be a healthy alternative both at nutritional and toxicological level. In addition, acrylamide concentration could even be reduced with simple mitigation operations before frying. © 2018 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 15 publications
1
8
0
2
Order By: Relevance
“…Equivalent acrylamide formation during the thermal treatment could therefore be promoted. For example, levels of 515 µg/kg in fried pumpkin chips and 225 µg/kg in fried carrot chips (no other ingredients were present) have been recently reported by Mesias et al (2018). In the present study, the acrylamide content in some of the vegetable chips (beet and carrot chips) were similar to those reported in French fries (Table 4).…”
Section: Acrylamide Levels In Snackssupporting
confidence: 87%
“…Equivalent acrylamide formation during the thermal treatment could therefore be promoted. For example, levels of 515 µg/kg in fried pumpkin chips and 225 µg/kg in fried carrot chips (no other ingredients were present) have been recently reported by Mesias et al (2018). In the present study, the acrylamide content in some of the vegetable chips (beet and carrot chips) were similar to those reported in French fries (Table 4).…”
Section: Acrylamide Levels In Snackssupporting
confidence: 87%
“…Chips also presented the greatest variability in acrylamide content, ranging from 23 to 1114 µg/kg, a pattern that is in line with data reported previously ( Table 2 ). Our own research group also documented this huge variability in the household setting (27–4200 µg/kg) [ 12 ], in catering services (<20–1068 µg/kg) [ 5 ] and in primary school canteens (20–4000 µg/kg) [ 17 ]. Sanny et al [ 18 ] reported similar results for restaurants (152–1023 µg/kg), institutional caterers (151–505 µg/kg) and chain fast food services (150–392 µg/kg).…”
Section: Resultsmentioning
confidence: 96%
“…In many cases, these food preparations are based on a protein source combined with cereals or potato. This type of food composition, when subjected to common culinary operations such as roasting, toasting, baking, or frying, can result in the development of the Maillard reaction within the food matrix and hence the formation of acrylamide [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Una medida de mitigación es un procedimiento basado en conocimientos científicos y técnicos actuales, que se aplica en la producción de alimentos a nivel industrial para mantener los valores de acrilamida por debajo de los niveles de referencia establecidos. Una de las formas de reducir la acrilamida de los alimentos es a través de cambios en los procedimientos industriales entre los que se encuentra la selección de materias primas con bajo contenido de asparragina y azúcares reductores, evitar la adición de azúcares reductores, el uso de aminoácidos competidores de asparragina (glicina,cisteína), el pretratamiento de materias primas, la modificación de técnicas de cocción, la reducción de pH, el uso de asparraginasa y la fermentación 44,45 .…”
Section: Organizaciones Internacionales Regulacionesunclassified
“…Tabla 4. Medidas de mitigación del contenido de acrilamida 44,45 . 1) Selección de materias primas con • Desarrollo de variedades de papa y trigo con concentraciones bajo contenido de asparragina y más bajas de asparragina libre y/o azúcares reductores, azúcares reductores mejorando las prácticas agronómicas.…”
Section: Conclusionesunclassified